Paclitaxel reduz o crescimento tumoral através da reprogramação de macrófagos associados ao tumor para o perfil M1 via TLR4 - Wanderley, Carlos Wagner de Souza (2018)
Paclitaxel (PCX) is an antineoplastic agent widely used to treat several solid tumor types. The primary mechanism of action of this drug is based on microtubule stabilization and induction of mitotic arrest leading to cells that proliferate rapidly to apoptosis. Here, was investigated whether PCX could reprogram the antitumor immune response by modulating the functional phenotype of tumor-associated macrophages (TAMs), as well as the involvement of TLR4 receptors on this process. Bone marrow macrophages from wild-type (WT) or TLR4 knockout mice in basal state of activation (naïve, M0) or previously polarized to M2-profile with IL-4 (10 ng/mL) were stimulated with PCX (10, 30, 100 μM) or LPS (100 ng/mL). After 48h, M1 and M2 markers of polarization status were measured by cytometry and ELISA. Furthermore, mice WT, TLR4 knockout or with a conditional deletion of TLR4 on macrophages (LysM-Cre+/-/TLR4fl/fl) were inoculated with murine breast cancer (4T1) or melanoma (B16) cell lines and treated with saline or PCX. Following, the tumors were harvested and the TAMs isolated by standard percoll (positive selection) for phenotype analysis by qRT-PCR. A bioinformatical analysis of an online database containing biopsy transcripts from patients with ovarian cancer obtained before and after 3 cycles of PCX therapy (GSE15622) was performed with focus on immunological signatures. In in vitro conditions, PCX polarized naive M0 macrophages to the M1-profile, blocked the M2-polarization and reprogrammed M2-polarized macrophages to the M1 phenotype in a TLR4-dependent manner, similarly to LPS. Accordingly, was observed that PCX played an antitumor effect through modulating the TAMs profile. Gene expression analysis of TAMs from tumors of PCX treated mice showed reduced expression of M2 markers (cd206, relmα, mmp9 and arg1) and up-regulation of M1 linked genes (Il12, inos and Il6). To confirm whether the PCX immune mechanism involved TAMs polarization via TLR4, we used mice selectively lacking TLR4 on macrophages (LysM-Cre+/-/TLR4fl/fl). Strikingly, the antitumor effect of PCX was significantly reduced in LysM-Cre+/-/TLR4fl/fl mice. Furthermore, the gene expression dataset analysis indicated an enrichment of genes linked to M1-profile in tumor biopsies from PCX treated patients. These findings indicate that PCX skews TAMs towards an M1 immunocompetent profile via TLR4 and this effect may contribute to the antitumor efficacy of PCX.